RUANG IDEAL BALI DALAM TEKANAN GLOBALISASI - I Putu Gede Suyoga (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
The development of space understanding in the Balinese architecture is deeply influenced by the theology, philosophy, and concepts of the Hinduism. Therefore, the real existence of the Balinese spatial layout is the grounding of the Hindu ideology. The Hindu teachings such as tat twam asi, bhuana agung - bhuana alit, panca maha bhuta, tri hita karana, tri bhuwana, purusha-pradhana, and others have been instilled in the practical principle of the Balinese architecture such as tri mandala, sanga mandala, tri angga, sukat ‘measurement’, natah, decoration, color, texture, and others. The Hindu spir- ituality in the Balinese and spatial architecture is manifested by: (1) Arrangement of the physical structure, building, landscape, anthropometry, topography, geography, and local climate, and aesthet- ics (form of yoga). (2) Various meanings and symbols on the spatial and physical layout of the building (form of yantra and tantra). (3) Procedures for building, accompanying rituals during pre-construc- tion, construction, and post-construction periods symbolize the ‘living building figures’ (mantra and mudra forms).